bDMARD can prevent the progression of AA amyloidosis to end-stage renal disease - Kvacskay, Peter; Hegenbart, Ute; Lorenz, Hanns-Martin; Schönland, Stefan; Blank, Norbert (Annals of the rheumatic diseases, 2024)
Introduction AA amyloidosis (AA) can be the consequence of any chronic inflammatory disease. AA is associated with chronic inflammatory diseases (cid+AA), autoinflammatory syndromes (auto+AA) or AA of unknown origin or idiopathic AA (idio+AA). The major organ manifestation is renal AA that can progress to end-stage renal disease (ESRD) and multiple organ failure. - Materials and methods This study is a monocentric retrospective analysis of the renal outcome and survival of patients with cid+AA (n=34), auto+AA (n=24) and idio+AA (n=25) who were treated with cytokine-inhibiting biological disease-modifying antirheumatic drugs (bDMARDs). - Results 83 patients with renal AA were identified and followed for a mean observational period of 4.82 years. C reactive protein (CRP), serum amyloid alpha and proteinuria were significantly reduced with bDMARD therapy. Progression to ESRD was prevented in 60% (cid+AA), 88% (auto+AA) and 81% (idio+AA) of patients. Tocilizumab was given to 34 patients with cid+AA and idio+AA and was more effective in reducing CRP and progression to ESRD and death compared with other bDMARDs. - Conclusions bDMARDs reduce systemic inflammation in various diseases, leading to a reduction of proteinuria and prevention of ESRD. Importantly, tocilizumab was more effective than other bDMARDs in controlling systemic inflammation in patients with chronic inflammatory diseases and idiopathic AA, leading to better renal and overall survival.